Evolution in endoscopic endonasal approach for the management of hypothalamic–pituitary region metastasis: A single-institution experience - Baiano, Cinzia; Somma, Teresa; Franca, Raduan Ahmed; Di Costanzo, Marianna; Scala, Maria Rosaria; Cretella, Pasquale; Esposito, Felice; Cavallo, Luigi Maria; Cappabianca, Paolo; Solari, Domenico (Frontiers in Oncology, 2022)
Introduction Endonasal endoscopic surgery has changed the treatment perspectives for different lesions of the hypothalamic–pituitary region. The metastases of the hypothalamic–pituitary region represent 0.4% of all intracranial metastatic tumors and account for only 1.8% of surgically managed pituitary lesions. The aim of tshis study is to describe a single-center institutional experience with 13 cases of hypothalamic–pituitary metastasis focused on presurgical workup, the evolution of the surgical technique, and postsurgical management according to our protocols, showing effects on progression-free and overall survival rates for this relatively uncommon location. Material and Methods We retrospectively reviewed the whole series of patients that received the endoscopic endonasal approach at the Division of Neurosurgery at the University of Naples “Federico II” undergoing surgery from January 1997 to December 2021. We identified 13 cases whose pathology reports revealed a metastatic lesion. Statistical analysis was performed to determine the Kaplan–Meier survival function and assess for log-rank differences in survival based on gender, surgical treatment, and postoperative therapy (p-value < 0.02*). Results The pathology report disclosed lung adenocarcinoma (six cases, 46%), breast adenocarcinoma (two cases, 15.4%), clear cell renal carcinoma (one case, 7%), melanoma (one case, 7%), colorectal adenocarcinoma (one case, 7%), uterine cervix carcinoma (one case, 7%), and follicular thyroid carcinoma (one case, 7%). A standard endoscopic endonasal approach was performed in 10 patients (76.9%), while an extended endonasal procedure was performed in only three cases (23%). Biopsy was the surgical choice in five patients with infiltrative and invasive lesions and a poor performance status (38%), while in the cases where neurovascular decompression was necessary, a subtotal resection was achieved in five patients (38%) and partial resection in three patients (23%). Recovery of visual field defect was observed in six of seven patients with visual loss (85.7%), improvement of oculomotor nerve palsy occurred in four of seven patients with this defect (57.1%), while the impairment of oculomotor palsy was observed in three patients (42.9%). Visual function was stable in the other patients. The median progression-free survival and overall survival were 14 and 18 months, respectively. There were statistically significant differences in PFS and OS in patients who underwent adjuvant radiotherapy (p=0.019 is referred to OS and p=0.017 to PFS, respectively; p-value = 0.02). Conclusions The endoscopic endonasal approach is a viable approach for the management of hypothalamic–pituitary metastases as this surgery provides an adequate opportunity to obtain tissue sample and neurovascular decompression, both being crucial for continuing the integrated adjuvant therapy protocols.